Предмет: Алгебра,
автор: doni13
Упростите выражение:2) (x+y)(x^2-xy+y^2)-x (x^2+y^2) 4) (c+3)(c^2-3c+9)-27
Ответы
Автор ответа:
0
(x+y)(x^2-xy+y^2)-x (x^2+y^2)=х^3+y^3+x^3-xy^2=x^6+y^3-xy^2
(c+3)(c^2-3c+9)-27=c^3+9-27=c^3-18
(c+3)(c^2-3c+9)-27=c^3+9-27=c^3-18
Автор ответа:
0
не за что)
Похожие вопросы
Предмет: Физика,
автор: StellaMacartni
Предмет: Информатика,
автор: Аноним
Предмет: Английский язык,
автор: dbdjsjajajah
Предмет: Математика,
автор: milkyway6985
Предмет: Обществознание,
автор: GTolyan497